The Role of Sharia Financial Literacy in Moderating the Relationship Between Herding Behaviour and Risk Tolerance Towards Sharia Stock Investment Decisions Among Gen Z Muslim Investor an Islamic Economic Perspective (A Study of Gen Z in Bandar Lampung City) - Alvinda Sugiarto; Ghina Ulfa Saefurrohman; Yulistia Devi (PT Syamilah Literasi Islami, 2025)
The phenomenon of increasing investment interest among Generation Z encourages the need for a deep understanding of the factors that influence investment decisions, especially in the context of Islamic economics. This study aims to analyze the influence of herding behavior and risk tolerance on sharia stock investment decisions among Generation Z Muslim investors in Bandar Lampung City, as well as to examine the role of sharia financial literacy as a moderating variable. The research method used a quantitative approach with Structural Equation Modeling (SEM) data analysis techniques based on Partial Least Square (PLS), with a sample size of 100 respondents. The results of the study indicate that herding behavior has a positive and significant influence on investment decisions, reflecting the tendency of Generation Z to follow group decisions in uncertain situations. Additionally, risk tolerance was also found to have a positive and significant influence on investment decisions, where higher risk tolerance leads to a greater tendency to make investment decisions. However, sharia financial literacy was unable to moderate the influence of herding behavior on investment decisions. Conversely, sharia financial literacy was found to strengthen the influence of risk tolerance on investment decisions, affirming its role in shaping more rational decisions aligned with sharia principles. This study contributes to the development of sharia financial literacy and wiser investment decision-making among young Muslims. These findings also provide an important foundation for policymakers and sharia financial industry players in designing more targeted education and marketing strategies.